Pattern recognition and image analysis : 8th Iberian Conference, IbPRIA 2017, Faro, Portugal, June 20-23, 2017, proceedings /: 8th Iberian Conference, IbPRIA 2017, Faro, Portugal, June 20-23, 2017, proceedings. (2017) - Unknown
No abstract available